Avaliação da performance de diferentes fontes de nitrogênio na produtividade e nutrição de citros - Devite, Gustavo Trevizan (Universidade Federal de São Carlos, 2023)
According to the source used, nitrogen fertilization alters the dynamics of the soil and its nutrients, which may cause acidification and exposure to the loss of basic cations. Orange trees have a high demand for these cations, such as calcium (Ca) for the leaves, a nutrient that can be easily leached with soil acidification. To evaluate the dynamics of nitrogen sources in orange production, this work was carried out in a commercial orchard with the Natal variety in Santa Cruz do Rio Pardo/SP, allowing the comparison of ammonium nitrate (NA) and calcium nitrate (NC) for leaf and flower nutrition, fruit quality, productivity (2022-2023 harvest) and physicochemical soil data. The sources were fertirrigated at a dose of 200 kg ha-1 of nitrogen, either alone (NA and NC) or in a mixture (NA+NC), the presence or absence of foliar fertilization with NC at a dose of 40 kg ha-1 of N. Each treatment was carried out in 8 repetitions of 25 plants, for each occurrence of foliar application. Data were analyzed in RStudio and means were analyzed for variance analysis and compared using Tukey's test at a 5% significance level. The treatment with NA + NC was the one that stood out the most among the analyzed results, with greater productivity and greater absorption of Ca in the leaves and flowers close to the NC. The NA + NC and NA treatments, both with a foliar application, were the ones that obtained the best results for Ca concentration and a sum of bases (SB) for the soil surface (layer 0-20 cm). For fruit quality, the results between treatments did not differ statistically.
Evaluation of the performance of different sources of nitrogen on productivity and nutrition of citrus
Keywords: Nitrato de amônio; Nitrato de cálcio; Citrumelo Swingle; Laranja Natal; Fertirrigação; Ammonium nitrate; Calcium nitrate; Swingle citrumelo; Natal sweet orange; Fertirrigation; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA